STRATEGI LEMBAGA PERS MAHASISWA DALAM PENGUATAN LITERASI POLITIK: STUDI MULTI-SITUS DI UNIVERSITAS PENDIDIKAN INDONESIA - Azzahra, Rahmah; Darmawan, Cecep; Setiawan, Mursyid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the strategies of student press organizations (Lembaga Pers Mahasiswa/LPM) in strengthening political literacy among university students at Universitas Pendidikan Indonesia (UPI). Employing a qualitative multi-site case study approach, research was conducted across four LPMs: Isolapos, Literat, UPP, and JMPS. Data were gathered through in-depth interviews with ten participants comprising LPM board members, active readers across faculties, and expert informants, supplemented by editorial observation and documentation study of 150 political content items published between January 2025 and June 2026. Findings reveal that each LPM applies a differentiated strategy shaped by the academic identity of its home study program, collectively producing a complementary ecosystem of political literacy strengthening. Isolapos applies a watchdog journalism strategy with campus-issue dominance; Literat employs a critical-literary analysis approach; UPP emphasizes civic education with constitutional references; and JMPS adopts an accessibility strategy with Gen-Z language. A notable finding is framing differentiation at the content-element level, wherein headline provocation coexists with balanced sourcing in the body text. The study also identifies a campus algorithmic paradox where the most substantive political content receives the lowest platform reach, as well as hidden deliberation, whereby meaningful political discussions migrate to private spaces beyond public engagement metrics. These findings enrich Rogers's communication strategy theory, Entman's framing theory, Crick's political literacy theory, and Habermas's deliberative democracy theory, while contributing new concepts to Civic Education scholarship.